INSURANCE BUSINESS AND RISK MANAGEMENT : AN EMPIRICAL STUDY ON GENERAL INSURANCE COMPANIES IN BANGLADESH - Mohammad Nazim Uddin Nazim Uddin; Manjurul Alam Mazumder; Mustafa Manir Chowdhury (Universitas Trisakti, 2014)
The importance of insurance business has been well recognized and emphasized in the risk management of individuals, trade, commerce and industry. The study examines the contribution of insurance business in risk management of Bangladesh. The study has used primary and secondary data. In order to collect primary data two sets of structural questionnaire are developed, which are prepared in the light of the objectives of the study. The secondary data are collected only relevant to the insurance business and risk management in Bangladesh for the theoretical development of the study. The data have been analyzed using statistical measures such as mean, ratio and 5 point- likert scale to validate the findings. This study revealed that the insurance business has made substantial effect for the risk management in Bangladesh. The study seems to carry an enormous academic value since a few studies have been undertaken in this area. It may be helpful to the regulatory body, insurance companies, Rating agency, Bangladesh insurance association, Bangladesh academy Academic researchers and national policy makers who have been making endeavour to improve insurance sector in developing countries as well as Bangladesh as a whole.Key Words: Insurance Business, Risk Management, Bangladesh